Assessment of thermodynamic stability of sapphire in eutectic molten chloride environment. Issue 5 (25th January 2022) - Thyagatur, Anugraha; Gakhar, Ruchi; Chidambaram, Dev; Calderoni, Pattrick; Buric, Michael; Mushongera, Leslie T.
Abstract: The continued development of molten salt reactors and concentrated solar power plants requires highly efficient and stable instruments that can efficiently monitor the chemical conditions of the molten salt during long‐term operation in both the fuel and coolant/heat transfer fluid loops. Sapphire (Al2 O3 ) fibers have shown tremendous potential due to inherent radiation resistance and a broader operational range of temperature. In this work, computational thermodynamic modeling (CALPHAD) using the ThermoCalc software in conjunction with the SGTE (Scientific Group Thermodata Europe) Molten Salts (SALT1) and Pure Substances (Pure5) databases is applied to understand the compatibility of Al2 O3 fibers with NaCl‐MgCl2 eutectic molten salt in the temperature range of 1500–2500 K. The thermodynamic calculations show that sapphire fibers are not expected to be stable over the long‐term when exposed to molten chloride salts at these temperatures. To improve the stability of these diagnostic fibers in molten salt environments, various pure metallic elements were evaluated as potential cladding materials for Al2 O3 fibers. Based on the thermodynamic analysis, molybdenum (Mo) and nickel (Ni) could be effective cladding materials to enhance the stability of Al2 O3 in NaCl‐MgCl2 chloride salt molten bath in the desired temperature range. Thus, the presence of Mo and Ni cladding can provide a protective coating against the corrosive molten salts, thus improving the stability of Al2 O3 . Additionally, it is also shown that Al2 O3 remains stable up to 2400 K in the presence of preexisting Al2 MgO4 and Al2 NiO4 in the eutectic molten chloride bath environment.